EVALUATION OF SOME TECHNICAL INDICATORS OF THE LOCALLY MODIFIED SHELLER FOR CORN GRAIN - & et al., Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out during 2017, at the factory of shelling corn grains at Al-musayyib /Babylon governorate. The objective of this study was to evaluate some technical indicators of the locally modified sheller for corn grain by using sheller machine locally modified with different peripheral speed of shelling cylinder 900, 1100 and 1300 m/min, different clearance between shelling cylinder and concave 23 and 28 mm on some the properties, such as sheller productivity, quality productivity, power consumption and unshelled grains. This research was done by applying the split plot design experiment within RCBD using four replicates. The results showed the following: clearance between shelling cylinder and concave 28 mm indicated significant superiority up on the clearance between shelling cylinder and concave 23 mm with highest sheller productivity (2.474 ton/h) and quality (193.735 kg.h.kw-1), while the clearance between shelling cylinder and concave 23 mm had lower power consumption 11.62 kw and lower percentage of unshelled grains 2.53%. The increasing in the peripheral speed of shelling cylinder from 900 to 1100 and 1300 m/min increased the sheller productivity, quality and power consumption. The peripheral speed of shelling cylinder (1300 m/min) indicated significant superiority up on the peripheral speed of shelling cylinder 900 and 1100 m/min in achieving higher sheller productivity 3.039 ton/h and higher quality productivity 205.061 kg.h/kw. while the peripheral speed of shelling cylinder 900 m/min achieving lower power consumption 11.78 kw and lower percentage of unshelled grains 2.37 %.